2020
DOI: 10.1021/acsomega.0c02224
|View full text |Cite
|
Sign up to set email alerts
|

Multiwalled Carbon Nanotube-N-Doped Graphene/Poly(3,4-ethylenedioxythiophene):Poly(styrenesulfonate) Nanohybrid for Electrochemical Application in Intelligent Sensors and Supercapacitors

Abstract: In this study, we reported the preparation of a conducting polymeric/inorganic nanohybrid consisting of multiwalled carbon nanotubes (MWCNT), N-doped graphene (NGr), and poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS), and its electrochemical application in intelligent sensors and supercapacitors. The multilayer thin film of the PEDOT:PSS-supported MWCNT-NGr nanohybrid was prepared by a facile layer-by-layer assembly strategy. The obtained conducting polymeric/ inorganic nanohybrid modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…39 Xue et al reported MWCNTs-N-Doped Graphene/PEDOT:PSS nanohybrid exhibited the C sp of 6.5 mF cm À2 . 40 The above literature survey indicated the utility of PEDOT:PSS as well as it composites with other materials in SC application. Previously, most of researches are dedicated toward the synthesis of PEDOT:PSS and rGO composites.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…39 Xue et al reported MWCNTs-N-Doped Graphene/PEDOT:PSS nanohybrid exhibited the C sp of 6.5 mF cm À2 . 40 The above literature survey indicated the utility of PEDOT:PSS as well as it composites with other materials in SC application. Previously, most of researches are dedicated toward the synthesis of PEDOT:PSS and rGO composites.…”
Section: Introductionmentioning
confidence: 94%
“…Liu et al reported the Ag‐coated Tyvek/PEDOT:PSS/CNTs composite electrodes for SC application which performed the higher C sp of 138.7 F g −1 39 . Xue et al reported MWCNTs‐N‐Doped Graphene/PEDOT:PSS nanohybrid exhibited the C sp of 6.5 mF cm −2 40 …”
Section: Introductionmentioning
confidence: 99%
“…It's known the layer‐by‐layer assembly in biosensing for the creation of biosensitive elements based on bacterial and yeast strains, [ 32 ] binding protein, [ 33 ] and aptamers. [ 34 ] The most commonly used layer‐by‐layer assembly based on electrostatic interactions using polyelectrolytes, [ 35–38 ] silver nanowires with oppositely charged part, [ 39 ] quantum dots, [ 40 ] carbon nanotubes, [ 41,42 ] and nanoparticles Bi/graphene oxide. [ 43 ] Described is the production through layer‐by‐layer electrodeposition of polyethylene and organometallic frameworks [ 44 ] and Au nanoparticles and polyelectrolytes.…”
Section: Layer‐by‐layer Approachmentioning
confidence: 99%
“…Thework range of the sensor is 0.2 ∼ 122.2 μM, and the LOD is 13.9 nM. Xue et al 25 prepare MWCNT-NGr/PEDOT: z E-mail: wenyangping1980@jxau.edu.cn; aisrong@163.com PSS/GCE nanosensor for amaranth. The response surface method is used for the optimization of five factors of the sensor, the linear range of the prepared sensor is 0.05 ∼ 10 μM and the LOD is 0.015 μM under the optimal conditions.…”
mentioning
confidence: 99%